Pengaruh Indeks Saham Syariah (ISSI) Terhadap Pertumbuhan Ekonomi di Indonesia - Itsnaini Chusnul Khotimah; Hairun Nisa; Darsi Ahmadan; Hidayani (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2024)
This study aims to analyze the effect of the Indonesia Sharia Stock Index (ISSI) on economic growth in Indonesia. The data used in this study are annual data from 2021 to 2023, obtained from the Indonesia Stock Exchange, the Central Statistics Agency (BPS), and the Financial Services Authority (OJK) of Indonesia. The analysis method used is simple linear regression with the help of EViews software. The dependent variable in this study is economic growth (GDP), while the independent variable is the Indonesian Sharia Stock Index (ISSI). The results showed that the Indonesian Sharia Stock Index (ISSI) had a significant and negative effect on economic growth, with the ISSI coefficient: -7.4401, which indicates a negative relationship between the Islamic Stock Index (ISSI) and economic growth in Indonesia. For every unit increase in ISSI, economic growth in Indonesia is estimated to decrease by 7.4401, assuming other variables are constant.